Caring with respect for the Human Dignity of institutionalized elderly people: a scoping review protocol - Lúcio Henriques, Liliana Vanessa (2020)
Objective: To map the existing literature on care with respect for the human dignity of institutionalized elderly. Method: Scoping review protocol, based on the methodology proposed by the Joanna Briggs Institute, considering the criteria defined and the adaptation to the type of databases/repository to be used. Results: The mapping of the evidence will make it possible to identify how the theme of care in the respect for the human dignity is approached, obtain information about population, type, design and context of studies and moments/practices that promote care in respect for human dignity. Conclusion: It is expected that this review will be a starting point for the analysis and systematization of studies related to care with respect to dignity, contributing to optimize practice and promote research in this thematic scope.